The Effect of Therapeutic Exercise in Postural Low Back Pain: A Case Report - Vivid Prety Anggraini; Sheilla Elfira San Pambayun; Pudji Hapsari, Rosalyna; Arya Pringga, Gutama (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Postural low back pain (LBP) is a non-specific LBP defined as pain or discomfort in low back areas caused by incorrect posture for ages. Most patients only experience mild and moderate pain from low back pain, however, it can cause chronic pain and disability for several groups. This case report aims to investigate the effect of therapeutic exercise on posture and pain in postural LBP. A 37-year-old male presented with LBP for 4 months with Numeric Rating Scale (NRS) 7. Physical examination showed impaired posture, wide base gait, limitation ROM of trunk, reduced breathing count test, muscle spasm at upper and lower back areas, positive in Thomas test, Ely test, and hamstring tightness test. The back pain functional scale (BPFS) was 7. The therapeutic exercise program consisted stretching exercises (neck, upper and lower back, hamstring, rectus femoris, iliopsoas muscle), core strengthening, William's flexion, McKenzie's, breathing and chest expansion exercise, alongside proprioceptive exercise. One cycle (eight times) of physical modalities, TENS at paralumbal and USD at paracervical, upper and middle trapezius, rhomboid, sternocleidomastoideus, paralumbal, and insertion of hamstring were given. We evaluated the patient's condition for about 4 months, and the patient showed a good compliance with improvement in pain score, ROM of the trunk, reduced muscle spasm and tightness, improved posture, gait, breathing, and BPFS. The patient can return to do his job again. This case report is able to demonstrate that therapeutic exercise improves clinical and functional conditions. These findings suggest the clinical implications of therapeutic exercise in patients with postural LBP are beneficial.